PENGARUH HARI PERDAGANGAN TERHADAP RETURN SAHAM DI BURSA EFEK JAKARTA - Eduardus Tandelilin; Algifari Algifari (Journal of Indonesian Economy and Business (JIEB), 1999)
The objectives of this study are: (1) to test the effect of trading days on stock return,(2) to determine whether there is any differences of daily stock returns, and (3) to testdaily abnormal return of some Indonesians common stocks. The results indicate thatthere is an effect of trading days on stock return. The study also shows that there isthe difference in daily stock returns. Finally, the result of the study indicates thatTuesday and Wednesday have an abnormal return.